Synthesis and biological evaluation of novel heteroring-annulated pyrrolino-tetrahydroberberine analogues as antioxidant agents. Issue 18 (1st October 2018) - Mari, Giacomo; Catalani, Simona; Antonini, Elena; De Crescentini, Lucia; Mantellini, Fabio; Santeusanio, Stefania; Lombardi, Paolo; Amicucci, Antonella; Battistelli, Serafina; Benedetti, Serena; Palma, Francesco
Graphical abstract: Abstract: Tetrahydroberberine (THB), otherwise known as canadine, is a natural alkaloid showing significant pharmacological properties and antioxidant protection against oxidative damage. Herein, we synthetized structurally complex THB analogues, namely pyrrolino-tetrahydroberberines (PTHBs)4a–g, containing the pyrrolino[2, 3 -b ]pyridine system, by means of the reactions of 1, 2-diaza-1, 3-dienes and 7, 8-dihydroberberine. Aim of the study was to explore the in vitro antioxidant properties of PTHBs in comparison to THB thus to identify the most effective against free radical-induced oxidative injury, by using three different antioxidant tests: the ORAC method, the DNA nicking assay, and the DCFH-DA cellular assay. As a result, PTHB4d emerged among the other THB analogues by exhibiting the best antioxidant properties. First, it was the only compound having an ORAC value completely comparable to that of THB, indicating the same ability to neutralize peroxyl radicals. Secondly, 4d showed an even better antioxidant capacity than THB in protecting DNA against ferrous ion-induced strand breaks. These observations were also confirmed in NCTC-2544 human keratinocytes exposed to hydrogen peroxide. Indeed, 4d protected cells against oxidation more efficiently than THB both in the short (1 and 3 h) and long (24 h) period of incubation, possibly suggesting increased cell membrane permeability and/or intracellular stability of4d as compared to THB.